Importance of Electrolytes in Exercise Performance and Assessment Methodology After Heat Training: A Narrative Review - Marcos S. Keefe; Courteney L. Benjamin; Douglas J. Casa; Yasuki Sekiguchi (Applied Sciences)
Performing exercise in hot environmental conditions presents athletes with potential negative physiological and perceptual implications. Key constituents, such as fluid and electrolytes, are lost during sweating through the process of cooling the human body. The loss of electrolytes impairs exercise performance. Heat training is one strategy to combat sweat electrolyte loss, with decreased sweat electrolyte concentration being a main sudomotor adaptation. To measure sweat electrolyte concentration, two common assessment methods are typically utilized: whole-body washdown and regional sweat patch measurements. The effects of physiological adaptations and sweat electrolyte assessment methodology have been investigated; however, the importance of methodological differences between sweat electrolyte measurements following heat training has yet to be explored. This review explores the differences between sweat electrolyte measurement techniques following adaptations incurred with heat training. Future research directions are also provided.